Pension Systems in East Africa : A Deep Dive - World Bank (World Bank, Washington, DC, 2020)
In this book, the authors share the East African story of pensions with the world. We have tried to give readers a perspective on the state of pensions within the EAC and contribute toward the development of the sector. We have also sought to provide practical advice to the business community that has embraced the opportunity to invest in pensions businesses across the region. We hope this publication will provide a useful guide not only to the history, but to the future of our pension systems. With well-thought through policies and robust implementation, we believe that East Africa can put in place pension systems fit for the 21st century and beyond. In so doing, the region can provide leadership and lessons for the rest of the world.